Estimation of the global burden of Mycobacterium tuberculosis lineage 1 - Thidarat Netikul (2022)
Tuberculosis is still problematic as it affects large numbers of people globally. Mycobacterium tuberculosis Lineage 1 (L1) or Indo Oceanic Lineage, one of widespread major lineages, has a specific geographic distribution and high mortality. It is highly diverse and endemic in several high burden countries. However, studies on the global burden of L1 and its sublineages remain limited. This may lead to the underestimation of the importance of its variance in developing and applying tuberculosis control measures. This study aimed to estimate the number of patients infected with M. tuberculosis L1 and its sublineages worldwide. The proportion of L1 among tuberculosis patients was searched in published reports from countries around the world and the number of patients was calculated based on a WHO report on country incidences and populations. The numbers of patients infected with the five major sublineages, namely L1.1.1, L1.1.2, L1.1.3, L1.2.1, and L1.2.2 were estimated where information was available. It was found that L1 accounted for 28% of global tuberculosis cases in 2012 and 2018. Over 80% of the L1 global burden was in India, the Philippines, Indonesia and Bangladesh, which are also among the countries with highest absolute numbers of tuberculosis patients in the world. Globally, the estimated number of patients infected with M. tuberculosis L1.2.1 and L1.1.2 was over 1.1 million and of patients infected with L1.1.1 was about 200,000. This study demonstrated that L1 contributes significantly to the global burden of tuberculosis. To achieve the End TB Strategy, more attention needs to be paid to the responses of M. tuberculosis L1 to various control measures.